Rockers - Bafaloukos, Ted; Wallace, Leroy; Rockers Film Corporation; Soundview Media Partners ([Kingston, Jamaica] : Rockers Film Corp., 1978)
Kingston's number one drummer buys a second-hand motorbike and takes a second job delivering record albums to help make ends meet. When it's learned that the bike has been stolen by the manager of the nightclub where he plays, he and some friends set out to recover it.
Originally released as a motion picture in 1978.
Starring Leroy Horsemouth Wallace.
Cinematographer, Peter Sova ; editor, Susan Steinberg.
In English with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Reggae music -- Jamaica; Reggae musicians -- Jamaica; Comedy films; Internet videos; Streaming video